Spontaneous splenic rupture from indeterminate dendritic cell proliferation: a case report. Issue 6 (7th June 2022) - Iqbal, Shaikh B; Chittal, Abhinandan R; Rao, Shiavax J; Lakra, Pallavi; Bhansali, Deepty; Pyrgos, George
Abstract: Spontaneous splenic rupture is a rare and life-threatening phenomenon, usually associated with an underlying infectious, inflammatory, hematological, neoplastic or rheumatologic condition. Indeterminate cell tumor is a rare neoplastic dendritic cell disorder that is poorly understood but shares immunophenotypic markers for Langerhans cells without Birbeck granules. A 73-year-old man presented with upper abdominal pain after an unwitnessed fall. Computed tomography angiography showed splenomegaly and a large ruptured splenic subcapsular hematoma. Intraoperative findings from an emergency laparotomy revealed a large hemoperitoneum and a ruptured spleen. Microscopic sections identified numerous, mostly poorly formed, small nodules classified as a proliferation of indeterminate dendritic cell tumors.